The adult stage of Paracloeodes charrua Emmerich & Nieto, 2009 (Ephemeroptera: Baetidae) - Lima, Lucas R.c.; Cruz, Paulo Vilela; Pinheiro, Ulisses (Zootaxa, 2013)
The genus Paracloeodes Day, 1955, included originally one new species, Paracloeodes abditus Day, 1955, known from nymphs and adults from the USA and one species transferred from Cloeodes Traver, 1938, P. portoricensis (Traver, 1938) from Puerto Rico. Later, McCafferty & Waltz (1990) synonymized the type species with Paracloeodes minutus (Daggy, 1945). Currently, the genus is represented in the New World by 19 species with 14 species reported from South America.